Major aspects of aesthetic sclerotherapy of hand veins - A. Yu. Semenov; V. V. Raskin (Амбулаторная хирургия)
Introduction. In recent years, phlebology centers have experienced an increasing inflow of patients presenting with a cosmetic issue related to bulging enlarged veins of the upper extremities. This issue especially affects people, whose jobs are associated with increased physical workloads to hands. A microfoam sclerobliteration procedure for eliminating hand veins has been performed in the phlebology center of the Medical Innovative Phlebological Center (MIPC, Moscow) since 2015. This procedure is indicated for patients with enlarged hand veins, which worsen the psycho-emotional condition of the patients. This study was aimed at developing the optimal method for conducting sclerotherapy of unaesthetic hand veins.Materials and methods. 38 patients (36 women and 2 men) have received sclerotherapy at the clinics of the Medical Innovative Phlebological Center from September 2015 to February 2020. The procedure was conducted using 1.5% to 2.5% lauromacrogol 400 microfoam. Each patient received 1 to 3 sclerotherapy sessions per hand with an interval of 3 to 7 days, the number of injections ranged from 1 to 5 per session.Results. All patients were followed over a period of 1 month to 1 year. Target veins were occluded in 100% of cases. Moderate hyperpigmentation in the projection of obliterated veins was observe in seven patients, after which it disappeared within 3 to 6 months.Conclusion. The aesthetic sclerotherapy of upper limbs is a safe and effective cosmetic procedure. After it is completed, the patients do not have any cicatrices, scars or stitches. Sclerotherapy provides demonstrates high cosmetic efficacy with minimal trauma. The procedure results in selective occlusion of targeted venous segments and makes it possible to preserve the cubital veins.